Sodium butyrate inhibits the expression of virulence factors in Vibrio cholerae by targeting ToxT protein - Sushmita Kundu; Suman Das; Priyanka Maitra; Prolay Halder; Hemanta Koley; Asish K. Mukhopadhyay; Shin-ichi Miyoshi; Shanta Dutta; Nabendu Sekhar Chatterjee; Sushmita Bhattacharya (mSphere)
ABSTRACT Cholera, a diarrheal disease caused by the gram-negative bacterium Vibrio cholerae, remains a global health threat in developing countries due to its high transmissibility and increased antibiotic resistance. There is a pressing need for alternative strategies, with an emphasis on anti-virulent approaches to alter the outcome of bacterial infections, given the increase in antimicrobial-resistant strains. V. cholerae causes cholera by secreting virulence factors in the intestinal epithelial cells. These virulence factors facilitate bacterial colonization and cholera toxin production during infection. Here, we demonstrate that sodium butyrate (SB), a small molecule, had no effect on bacterial viability but was effective in suppressing the virulence attributes of V. cholerae. The production of cholera toxin (CT) was significantly reduced in a standard V. cholerae El Tor strain and two clinical isolates when grown in the presence of SB. Analysis of mRNA and protein levels further revealed that SB reduced the expression of the ToxT-dependent virulence genes like tcpA and ctxAB. DNA-protein interaction assays, conducted at cellular (ChIP) and in vitro conditions (EMSA), indicated that SB weakens the binding between ToxT and its downstream promoter DNA, likely by blocking DNA binding. Furthermore, the anti-virulence efficacy of SB was confirmed in animal models. These findings suggest that SB could be developed as an anti-virulence agent against V. cholerae, serving as a potential alternative to conventional antibiotics or as an adjunctive therapy to combat cholera.IMPORTANCEThe world has been facing an upsurge in cholera cases since 2021, a similar trend continuing into 2022, with over 29 countries reporting cholera outbreaks (World Health Organization, 16 December 2022, Disease Outbreak News, Cholera—global situation). Treatment of cholera involves oral rehydration therapy coupled with antibiotics to reduce the duration of the illness. However, in recent years, indiscriminate use of antibiotics has contributed to the emergence of antibiotic-resistant strains. In this study, we have addressed the problem of antibiotic resistance by targeting virulence factors. Screening various compounds using in silico methods led to the identification of a small molecule, SB, that inhibits the virulence cascade in V. cholerae. We demonstrated that (i) SB intervened in ToxT protein-DNA binding and subsequently affected the expression of ToxT-regulated virulence genes (ctxAB and tcpA) and (ii) SB is a potential therapeutic candidate for the development of a novel antimicrobial agent.